全球視野在地化的校務研究：以國立臺灣大學經驗為例 Think Globally and Act Locally: National Taiwan University's Experience of Institutional Research - 李紋霞 Jennifer Wen-Shya Lee; 符碧真 Bih-Jen Fwu (National Taiwan Normal University, 2017)
過去我國的大學經營常是「跟著感覺走」，但在校園民主化後，校務決策應以「證據」為本。2015 年在教育部推動下，許多大學成立校務研究（Institutional Research, IR）辦公室進行相關工作。美國校務研究發展出成熟的運作模式，成為全球高等教育的典範，惟校務研究需高度與所處的區域、校園環境脈絡結合，故如何具有全球視野在地化的思維，從事植基於校園文化的 IR 工作，以解決自己的問題，是當前要務。本文以廣為學界引用的校務研究三種組 織智能與五種角色功能面貌，檢視與反思國立臺灣大學過去 10 年發展全球視野在地化 IR 工作的過程和挑戰，供各校未來推動 IR 工作的參考。 Previously, university management in Taiwan was often guided by common sense or decision-makers' intuition. However, because university governing bodies have become more democratic, policymaking need to be more evidence based. In 2015, with the promotion of the Ministry of Education, many universities established institutional research (IR) offices to support evidence-based policymaking. The mature U.S. IR model has long been considered a global standard. However, because each university has its own campus culture and governance style, the U.S. model must be adapted and modified to suit Taiwanese universities. The major objective of IR is to think globally and act locally by maintaining a global perspective, staying informed of local concerns, and working within regional constraints. By using the well-cited frameworks of three organizational intelligences and five IR faces, this paper examined and reflected on the processes and challenges of IR at National Taiwan University (NTU). NTU's experience may provide insights into future IR development in Taiwanese higher education.